Kadar Estrogen Darah dan Tingkat Keasaman (pH) Mukus Serviks Sapi Aceh Memengaruhi Daya Penetrasi Spermatozoa - Panjaitan, Budianto; Pambudi, Ridho; Amansyah, Romi; Akmal, Muslim; Siregar, Tongku Nizwan (Jurnal Veteriner; Vol 21 No 3 (2020), 2020)
This research has purposes to determine the relationship between estrogen levels and aceh cattle cervical mucus pH on spermatozoa penetration. This study used eight aceh cows aged 3-7 years old and had a body weight of 150-250 kg, had already been delivered, and has two regular cycles. All cows were given a synchronization treatment using prostaglandin F2á (PGF2á) at   a dose of 25 mgs with single injection. A collection of cervical mucus was performed during the first cervical mucus discharge, which is about 8-16 hours after the initial onset of symptoms. Cervical mucus samples were collected by aspiration method. The pH of the cervical mucus was measured in the laboratory using a universal indicator pH (Nesco).The estrogen concentration was measured by enzyme linked immunosorbant assay (ELISA) method. Measurement of spermatozoa penetration power by calculating the distance of spermatozoa travel from the beginning where spermatozoa drops to reach the furthest distance. Spermatozoa penetration was observed with a microscope for 30 minutes. The data of the research were analyzed descriptively. The pH value of cervical mucus of aceh cattle was 6.0-9.0. The distribution data of pH cervical mucus of  6.0; 7.0; 8.0 and 9.0  were 1, 2, 4, and 1, average spermatozoa penetration at pH 6.0; 7.0; 8.0 and 9.0 is 10.0; 25.0±32.53; 10.5±15.70; and  12.0 mm. The estrogen concentration in viscosity of thick cervical mucus; medium; and dilute are 29.39±6.29; 23.24±4.62; and 30.93 pg/ml with a spermatozoa penetration strength rate of 14.8±19.11; 3.0±1.41; and 34.0 mm. The results of statistical analysis showed correlation between estrogen concentration (x) and spermatozoa penetration distance (y) in aceh cattle was 0.328 with regression equation y= 26.44 + 0.11x (P>0,05). In conclusion pH of aceh cattle cervical mucus affect the spermatozoa penetration. The best spermatozoa penetration is obtained at cervical mucus at pH 7. There is relationship enough between estrogen concentration and spermatozoa penetration in aceh cattle.